PENGARUH DEBT TO EQUITY RATIO PADA RETURN SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Purwitajati, Endah; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study was conducted to determine the effect on stock returns DER well as the size ofthe company as a moderating variable DER influence on stock returns. Samples consist of property and real estate companies listed on the Indonesian Stock Exchange (BEI) in 2010-2014 were taken by purposive sampling of 48 companies, but only 25 companies that could be usedas a sample. This research was conducted during 5 years of observation so that the data obtained as many as 125 samples. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that the DER positive effect on stock returns. The size of the company used as a moderating variableis declared capable of moderate to weaken the positive effect on stock returns DER.
Keywords: DER, Company Size, Return Shares